Comparison of the bioavailability and adhesiveness of different rotigotine transdermal patch formulations. (December 2013) - Elshoff, Jan-Peer; Timmermann, Lars; Schmid, Miriam; Arth, Christoph; Komenda, Michael; Brunnert, Marcus; Bauer, Lars
Abstract Objective: Rotigotine transdermal patch is approved for the treatment of early and advanced idiopathic Parkinson's disease (PD) and moderate-to-severe idiopathic restless legs syndrome (RLS). A cold chain manufacturing and distribution process was temporarily implemented in 2008, as this reduced the crystal formation reported within patches stored at room temperature. In order to overcome the crystallization issue and meet EMA and FDA requirements, a new room temperature stable formulation was developed. The three studies reported here were conducted to determine whether the new room temperature stable patch demonstrated similar bioavailability and adhesiveness to the original and intermediate patches. Methods: Data are reported from three cross-over studies that compared the original, cold chain and room temperature stable patch. Two open-label bioequivalence studies investigated the 2 mg/24 h dosage in healthy individuals (SP951, n = 52 [Clinicaltrials.gov: NCT00881894]; SP0987, n = 50 [NCT01059903]) and a double-blind patch adhesiveness study investigated the 8 mg/24 h dosage in patients with PD (SP1066, n = 56 [NCT01338896]). Results: Plasma concentration–time curves and geometric means for pharmacokinetic parameters were similar for the cold chain vs. original patch in SP951 (AUC(0–tz): 2.68 vs. 2.71 ng/mL*h; point estimate: 0.99 [90% confidence interval (CI): 0.91, 1.07]) (Cmax: 0.131 vs. 0.136 ng/mL; 0.96 [0.89, 1.04]) and for the room temperature stable vs. cold chain patch in SP0987 (AUC(0–tz): 4.51 vs. 4.87 ng/mL*h; 0.90 [0.84, 0.97]) (Cmax: 0.23 vs. 0.23 ng/mL; 0.95 [0.88, 1.02]). In both studies, 90% CIs for ratios of AUC(0–tz) and Cmax were within the bioequivalence acceptance range (0.8–1.25). In SP1066, overall median adhesiveness scores were similar for cold chain (0.5 [range: 0–4]) and room temperature stable (0 [0–4]) formulations. Conclusion: These results demonstrated bioequivalence and indicated similar adhesiveness of the approved room temperature stable rotigotine patch with the original and cold chain patches. Potential limitations include the enrolment of healthy volunteers in the bioequivalence studies, as these individuals were likely to be younger than the general PD or RLS population.